Proteomic Profiling of Plasma and Total Blood Exosomes in Breast Cancer: A Potential Role in Tumor Progression, Diagnosis, and Prognosis - Tutanov, Oleg; Proskura, Ksenia; Kamyshinsky, Roman; Shtam, Tatiana; Tsentalovich, Yuri; Tamkovich, Svetlana (Frontiers in Oncology, 2020)
Exosomes are directly involved in governing physiological and pathological processes of an organism by horizontal transfer of functional molecules (proteins, microRNA, etc.) from producing to receiving cells. We explored the relationship of proteins from plasma exosomes, and exosomes from the total blood of healthy females (HFs) and breast cancer patients (BCPs), with crucial steps of tumor progression: EMT, cell proliferation, invasion, cell migration, stimulation of angiogenesis, and immune response. A proteomic analysis of exosomes isolated from samples using ultrafiltration and ultracentrifugation was performed. Their nature has been verified using cryo-electron microscopy and flow cytometry. Bioinformatics analysis showed that 84% of common exosomal proteins were of cytoplasmic and vesicle origin. They perform functions of protein binding and signaling receptor binding, and facilitated the processes of the regulated exocytosis and vesicle-mediated transport. Half of the identified exosomal proteins from blood of HFs and BCPs are involved in crucial steps of the tumor progression: EMT, cell proliferation, invasion, cell migration stimulation of angiogenesis, and immune response. Moreover, we found that protein cargo of exosomes from HF total blood was enriched with proteins inhibiting EMT, cell migration, and invasion. Tumor diagnostic/prognostic protein markers accounted for 47% of the total composition of cell-surface-associated exosomes (calculated as the difference between the total blood exosomes and plasma exosomes) from BCP blood. Breast cancer-associated proteins were equally represented in the blood cell-surface-associated exosomes and in the plasma exosomes from BCPs. However, hyper-expressed proteins predominate in the blood cell-surface-associated exosomes as compared to the plasma exosomes (64 vs. 14%). Using breast cancer proteins data from the Human Protein Atlas (HPA) (www.proteinatlas.org/), three favorable (SERPINA1, KRT6B, and SOCS3), and one unfavorable (IGF2R) prognostic protein markers were found in the BCP total blood exosomes. Identified exosomal proteins from BCP blood can be recommended for further testing as breast cancer diagnostic/prognostic biomarkers or novel therapeutic targets.